ENHANCE A POWER TRANSFORMER INTERFERENCE PROTECTION AT SUBSTATIONS - Suranta Putra Tarigan; Solly Aryza; Adi Sastra P. Tarigan (Sean Institute, 2022)
The problem that is often caused by the palm oil industry is the disposal of liquid waste which causes air pollution due to the pungent smell from the waste pool. If it is thrown into the river it will pollute the river and if it is thrown into the ground then the soil will be contaminated. Then an analytical study was conducted so that the liquid waste can be processed by analyzing methane gas whose raw material is liquid waste that is processed anaerobically to fuel the Biogas Power Plant. One of the large plantation potentials obtained from Palm Oil Mills (PKS), which processes Palm Oil Fresh Fruit Bunches (FFB) into Crude Palm Oil (CPO), is biomass waste with a fairly large amount in the form of organic waste in the form of empty coconut bunches. palm oil (Tankos), shells and coir, and liquid waste (Palm Oil Mill Effluent/POME). POME has high energy potential, but in general it has not been used optimally. POME is decomposed in sewage ponds left to decompose naturally. Converting POME into biogas to be burned can produce energy while reducing the impact of climate change. This gas appears as a result of the anaerobic breakdown of organic compounds. Organic liquid waste generated during palm oil production is a major energy source that has not been widely utilized in Indonesia. Converting POME into biogas to be burned can produce energy while reducing the impact of climate change.